Accumulation of iron by yersiniae. - Perry, R D (1979)
Escherichia coli, Bacillus megaterium, and three species of yersiniae grew rapidly without significant production of soluble siderophores in a defined iron-sufficient medium (20 microM Fe3+). In iron-deficient medium (0.1 to 0.3 microM Fe3+) all organisms showed reduced growth, and there was extensive production of siderophores by E. coli and B. megaterium. Release of soluble siderophores by Yersinia pestis, Y. pseudotuberculosis, or Y. enterocolitica in this medium was not detected. Citrate (1 mM) inhibited growth of yersiniae in iron-deficient medium, indicating that the organisms lack an inducible Fe3+-citrate transport mechanism. Uptake of 59Fe3+ by all yersiniae was an energy-dependent saturable process, showing increased accumulation after adaptation to iron-deficient medium. Growth of Y. pseudotuberculosis and Y. enterocolitica but not Y. pestis on iron-limited solid medium was enhanced to varying degrees by exogenous siderophores (desferal, schizokinen, aerobactin, and enterochelin). Only hemin (0.1 pmol) or a combination of inorganic iron plus protoporphyrin IX promoted growth of Y. pestis on agar rendered highly iron deficient with egg white conalbumin (10 microM). Growth of Y. pseudotuberculosis and Y. enterocolitica was stimulated on this medium by Fe3+ or hemin. These results indicate that hemin can serve as a sole source of iron for yersiniae and that the organisms possess an efficient cell-bound transport system for Fe3+.